2021
DOI: 10.1186/s13148-021-01103-8
|View full text |Cite
|
Sign up to set email alerts
|

The role of epigenetic mechanisms in the regulation of gene expression in the cyclical endometrium

Abstract: Background The human endometrium is a highly dynamic tissue whose function is mainly regulated by the ovarian steroid hormones estradiol and progesterone. The serum levels of these and other hormones are associated with three specific phases that compose the endometrial cycle: menstrual, proliferative, and secretory. Throughout this cycle, the endometrium exhibits different transcriptional networks according to the genes expressed in each phase. Epigenetic mechanisms are crucial in the fine-tun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
46
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(46 citation statements)
references
References 228 publications
0
46
0
Order By: Relevance
“…Mechanisms of epigenetic regulation, such as DNA methylation, noncoding RNAs and histone post-translational modifications induce the expression of genes associated with stromal cell proliferation, endometrial epithelial growth, transcriptional regulation, and angiogenesis. During decidualization and implantation, epigenetic remodeling occurs in epithelial and stromal cells, leading to rearrangement of gene expression and cell function [ 42 ]. In this study, we showed that expression of miR-34a, miRNA-223, and miRNA-125b is significantly lower in endometrial tissue of patients with reproductive pathologies compared to endometrial tissue from control females.…”
Section: Discussionmentioning
confidence: 99%
“…Mechanisms of epigenetic regulation, such as DNA methylation, noncoding RNAs and histone post-translational modifications induce the expression of genes associated with stromal cell proliferation, endometrial epithelial growth, transcriptional regulation, and angiogenesis. During decidualization and implantation, epigenetic remodeling occurs in epithelial and stromal cells, leading to rearrangement of gene expression and cell function [ 42 ]. In this study, we showed that expression of miR-34a, miRNA-223, and miRNA-125b is significantly lower in endometrial tissue of patients with reproductive pathologies compared to endometrial tissue from control females.…”
Section: Discussionmentioning
confidence: 99%
“…The stroma retains clonogenic properties of mesenchymal stem cells [ 35 , 36 ]. Cyclic modulation of endometrium may be controlled in part by epigenetic mechanisms [ 37 ]. With aging, the function of endometrium is affected by the loss of stem cells [ 38 ] as well as by decreased proliferation necessary for establishing implantation, driven by lower estrogen production.…”
Section: Discussionmentioning
confidence: 99%
“…High levels of progesterone in the post-ovulatory phase modulate the endometrial gene expression required for implantation by regulating DNA methylation [75][76][77], and alterations in the DNA methylation of 448 sites have been associated with defective endometrial receptivity and consequently in recurrent pregnancy failure [75,78]. Moreover, different non-coding transcripts like lncRNAs and miRNAs are involved in endometrial receptivity regulation [79].…”
Section: Pre-receptive and Receptive Endometriummentioning
confidence: 99%